The Prognostic Importance of Impaired Fasting Glycemia in Chronic Coronary Heart Disease Patients - Slezák, David; Mayer, Otto; Bruthans, Jan; Seidlerová, Jitka; Rychecká, Martina; Gelžinský, Julius; Mateřánková, Markéta; Karnosová, Petra; Wohlfahrt, Peter; Cífková, Renata; Filipovský, Jan (Experimental and Clinical Endocrinology & Diabetes, 2018)
Objectives Impaired glucose metabolism represents one the most important cardiovascular risk factors, with steeply raising prevalence in overall population. We aimed to compare mortality risk of impaired fasting glycaemia (IFG) and overt diabetes mellitus (DM) in patients with coronary heart disease (CHD).Study design prospective cohort studyMethods A total of 1685 patients, 6–24 months after myocardial infarction and/or coronary revascularization at baseline, were followed in a prospective cohort study. Overt DM was defined as fasting glucose ≥ 7 mmol/L and/or use of antidiabetic treatment, while IFG as fasting glucose 5.6–6.99 mmol/L, but no antidiabetic medication. The main outcomes were total and cardiovascular mortality during 5 years of follow-up.Results During follow-up of 1826 days, 172 patients (10.2%) deceased, and of them 122 (7.2%) from a cardiovascular cause. Both exposures, overt DM (n=623, 37.0% of the whole sample) and IFG (n=436, 25.9%) were associated with an independent increase of 5-year total mortality, compared to normoglycemic subjects [fully adjusted hazard risk ratio (HRR) 1.63 (95%CI: 1.01–2.61)]; p=0.043 and 2.25 (95%CI: 1.45–3.50); p<0.0001, respectively]. In contrast, comparing both glucose disorders one with each other, no significant differences were found for total mortality [HRR 0.82 (0.53–1.28); p=0.33]. Taking 5-years cardiovascular mortality as outcome, similar pattern was observed [HRR 1.96 (95%CI: 1.06–3.63) and 3.84 (95%CI: 2.19–6.73) for overt DM and IFG, respectively, with HRR 0.63 (95%CI: 0.37–1.07) for comparison of both disorders].Conclusions Impaired fasting glycaemia adversely increases mortality of CHD patients in the same extent as overt DM.
Keywords: pre-diabetes; secondary prevention; total mortality; fatal vascular events; EUROASPIRE